2018
DOI: 10.7759/cureus.2158
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Related Candida Endocarditis on the Right Atrial Septum – A Case Report

Abstract: The use of subcutaneous catheter devices has increased over the past two decades along with its associated infections. One of the complications is infective endocarditis (IE), which usually occurs on the valves of the heart. However, IE can rarely occur on the atrial septal wall. The most common pathogens associated with catheter-related IE are staphylococcus bacteria, and it is rarely caused by fungi. We present a case of a 75-year-old Caucasian female with infective endocarditis located on the right side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Secondary cardiac metastases occur 20 times more often, the most common primaries being mesothelioma, lung cancer, and melanoma [4]. Primary atrial mural endocarditis is rare with reported organisms including staphylococcus species, streptococci species, aspergillus, and candida [2,[5][6][7]. Secondary infection complicating myxoma has also been reported with similar bacterial pathogens [8].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary cardiac metastases occur 20 times more often, the most common primaries being mesothelioma, lung cancer, and melanoma [4]. Primary atrial mural endocarditis is rare with reported organisms including staphylococcus species, streptococci species, aspergillus, and candida [2,[5][6][7]. Secondary infection complicating myxoma has also been reported with similar bacterial pathogens [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, the location and association to a particular valve are dependent on a wide array of risk factors. For instance, a case report about C. albicans in a 75-years-old female using subcutaneous catheter devices found that there was no valve involvement; it seemed that the right atrial septum was involved [15]. This rare case depicted the propensity of C. albicans to implant itself on any location of the endothelium [15].…”
Section: Anatomymentioning
confidence: 98%
“…For instance, a case report about C. albicans in a 75-years-old female using subcutaneous catheter devices found that there was no valve involvement; it seemed that the right atrial septum was involved [15]. This rare case depicted the propensity of C. albicans to implant itself on any location of the endothelium [15]. Another case report supports this theory; this report depicted a foreign body, a fishbone, leading to left atrial C. albicans infective endocarditis as a result of its penetration through the esophagus [28].…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Other, less common, sites of infection have also been described, such as the right atrial septum, right ventricular cavity, and left atrial cavity. [22][23][24][25][26] Exogenous material in the body, such as CEID, are particularly susceptible to infection with C albicans as the microorganism produces a highly organized biofilm covered in an extracellular matrix that facilitates binding. [27][28][29] Multiple cases of CEID lead infections have been reported in the literature.…”
Section: A S E Rep Ortmentioning
confidence: 99%